Association between neutrophil-to-high-density lipoprotein cholesterol ratio and non-alcoholic fatty liver disease or metabolic dysfunction-associated steatotic liver disease: evidence from NHANES 2017–2020 - Na Zhu; Yanyan Li; Yingying Lin; XinYu Cui; Xin Li; Xin Li (Frontiers in Medicine)
BackgroundNon-alcoholic fatty liver disease (NAFLD) or metabolic dysfunction-associated steatotic liver disease (MASLD) is closely associated with chronic inflammation and lipid metabolism disorders. The neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) is an integrative marker reflecting inflammatory responses and lipid metabolism disorders and is associated with various diseases. This cross-sectional study aimed to determine the association between NHR and NAFLD, MASLD, and liver fibrosis.MethodsData for this study were obtained from the 2017–2020 National Health and Nutrition Examination Survey (NHANES), we employed weighted multiple regression and restricted cubic spline (RCS) analysis to assess the relationship between NHR and NAFLD, MASLD, and liver fibrosis. Additionally, we performed stratified analyses based on gender, age, body mass index, diabetes, hypertension, smoking status, and history of cardiovascular disease to evaluate the consistency of these associations across different subgroups.ResultsA total of 6,526 participants were included in the study. 2,839 (weighted 44.1%) participants were diagnosed with NAFLD and 2,813 (weighted 43.7%) participants were diagnosed with MASLD. After adjusting for confounders, NHR was positively associated with the risk of NAFLD/MASLD, and the correlation was particularly significant in the subgroups of females, those without hypertension, and those without diabetes (p < 0.05). By the NHR quartile, the risk of NAFLD/MASLD increased progressively with higher NHR levels (P for trend <0.001). In addition, RCS analysis showed a nonlinear association between NHR and NAFLD/MASLD and liver fibrosis (P-non-linear <0.05).ConclusionNHR may serve as a potential marker for NAFLD/MASLD and liver fibrosis, and lowering NHR levels could help reduce the incidence of these conditions.